2007
DOI: 10.1007/s11896-007-9002-7
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Blue Line: Investigating Police Officers’ Attitudes Toward Rape

Abstract: The current study contributes to what is known about police officers" attitudes toward rape. A survey was administered to 891 sworn police officers in two states in the southeastern United States. The surveys were designed to assess police officers" acceptance of rape myths. It was hypothesized that police officers would be accepting of rape myths, which are inherently misogynistic. Attitudes toward rape were expected to vary according to educational attainment and experience with rape investigations, such tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
133
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 29 publications
7
133
1
1
Order By: Relevance
“…5. For a more detailed analysis of responses on the RMA-R and VCS, as well as differences in responses between male and female police officers, see (Page, 2007).…”
Section: Author's Notementioning
confidence: 99%
“…5. For a more detailed analysis of responses on the RMA-R and VCS, as well as differences in responses between male and female police officers, see (Page, 2007).…”
Section: Author's Notementioning
confidence: 99%
“…The latter is reflected by LeDoux and Hazelwood (1985) who found that police officers had in general a low adherence to some rape myths. Page (2008) also found that police officers who were higher in rape myth acceptance were less likely to believe a victim who did not match the "real" rape stereotype compared to police officers who had lower or moderate rape myth acceptance (see also Lee, Lee, & Lee, 2012). Furthermore, male police officers have been demonstrated to accept rape myths at a higher level than did female police officers (Brown & King, 1998;Page, 2007).…”
mentioning
confidence: 91%
“…Such a role can have a significant impact on the progression of rape cases through the criminal justice system (Spohn & Tellis, 2012). However, there has been very little research examining police officer rape myth acceptance (Lonsway, Welch, & Fitzgerald, 2001;Page, 2008), demonstrating the importance of conducting research on this topic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a now a considerable evidence base that suggests that women officers: are less aggressive, use less force and adopt less confrontation styles in their interactions (Brown and Langan, 2001;McElvain and Kposowa, 2008;Waugh et al , 1998;Rabe-Hemp, 2008, 2009Schuck and Rabe-Hemp, 2005); adopt a higher ethical code of conduct ( Brereton, 1999;Corsianos, 2011;Lonsway, Wood and Spillar, 2000;Waugh, Ede & Alley, 1998;Fleming & Lafferty, 2003; demonstrate greater empathy and communication skills in serving the needs to women and children, especially those subject to violent or sexual abuse (Brown and King, 1998;Page, 2007;Schuller and Stewart, 2000;Sun 2007); have stronger relations with the community (Miller, 1999;Brown and Woolfenden, 2011; are better equipped in developing positive long term relationships in partnership working (O'Neil and McCarthy, 2012); and adopt more transformational leadership styles than their male counterparts (Brown, 2007;Silvestri, 2003and Heidensohn, 1992Rabe-Hemp, 2008;Whittred, 2008).…”
Section: Diversity and Human Rights Strategy For The Police Service (mentioning
confidence: 99%